2020
DOI: 10.1155/2020/4915812
|View full text |Cite
|
Sign up to set email alerts
|

A New Reliability Model Based on Lindley Distribution with Application to Failure Data

Abstract: Software reliability is an important feature that influences systems’ reliability. Software reliability models are a common tool to evaluate software reliability quantitatively. Various reliability models have been suggested based on the NHPP (nonhomogeneous Poisson process). In this article, a new NHPP model based on the Lindley distribution is proposed. The mathematical formulas for its measures of reliability are obtained and graphically illustrated. The proposed model’s parameters are estimated using both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…12 The Pham-Zhang (PZ) model, which The authors in 13 presented, is an Sshaped nondecreasing inflection model with an exponential error introduction rate function. Al-Turk 14 has suggested a novel NHPP model centered on log-logistic model. The efficiency of the Weibull distribution features was investigated by Xiao and Dohi.…”
Section: Introductionmentioning
confidence: 99%
“…12 The Pham-Zhang (PZ) model, which The authors in 13 presented, is an Sshaped nondecreasing inflection model with an exponential error introduction rate function. Al-Turk 14 has suggested a novel NHPP model centered on log-logistic model. The efficiency of the Weibull distribution features was investigated by Xiao and Dohi.…”
Section: Introductionmentioning
confidence: 99%
“…The research on the reliability of CNC machine tools has become increasingly systematic and diversified (2019). Regarding reliability modeling, to estimate the distribution type of failure time, Al-Mutairi et al (2020) suggested multiple reliability models based on NHPP, and the new models performed well when applied to failure data. Aminisharifabad et al (2021) proposed a model parameter estimation method based on the partial likelihood framework to make the traditional parameter estimation method and the maximum likelihood estimation method suitable for the model in this paper.…”
Section: Introductionmentioning
confidence: 99%